Potencial de extratos à base de Calendula officinalis L. na indução de resistência e no efeito fungistático sobre Botrytis cinerea, in vitro - Fogolari, Hoilson (2010)
Several studies have demonstrated the potential of medicinal plants in the pathogens control, through its direct fungistatic action or its ability to induce plant defense, it suggesting the presence of molecules with characteristics elicitors. Three experiments were carried out on 2009 and 2010, in the Universidade Tecnológica Federal do Paraná, Dois Vizinhos city (PR – Brazil). The aim of this work was to evaluate prepared caledula (Calendula officinalis L.) potential for phytoalexins induction in the soybean cotyledons, resistance induction in the strawberry fruits and fungistatic effect of Botrytis cinerea in vitro. The experimental design was completely randomized with 15 treatments resulting from the combination of three forms of extraction (alcohol extract, infusion and maceration) and five concentrations (zero, 1.25, 2.5, 5 and 10%), with zero concentration distilled water in a factorial (3 x 5) with four replications the distilled water was used as control. The first experiment evaluated the potential fungistatic preparations in the B. cinerea control. The preparations with the different concentrations were put in Petri dishes with BDA culture media. After the media solidification, a hole of 8 mm was punched in the dishes Petri center and in this hole was introduced 2μL of spore B. cinerea suspension. The Petri dishes were kept in growth chamber for 7 days at 25°C. In the seventh day, the halo diameter fungus growth was evaluated. The second experiment evaluated the phytoalexins induction in the soybean cotyledons soybean as result of C. officinalis derivatives. Soybean seeds were sown in sterilized sand and it were kept at room temperature during 10 days. Then, the seedlings cotyledons were removed and on the abaxial part it was applied the treatments. After methodological procedures of extraction technique, it was obtained the phytoalexins glyceolin quantification by for spectrophotometry. The third study evaluated the C. officinalis solutions effect on the strawberry fruits physic-chemical and biochemical characteristics. The fruits were packed in plastic trays and it sprayed with different treatments. After six hours of the treatments spraying, it was sprayed a solution containing about 10-4 spore of B. cinerea fungus. After 3 days, it was realized the evaluations. The mass loss, rots incidence, titratable acidity, flesh firmness, total soluble solids, totals sugars, anthocyanins, flavonoids and activity of phenylalanine-amonialiase (PAL) were evaluated. The results showed that the maceration with all over the concentrations used, it inhibited of the B. cinerea fungus in vitro growth. Concentrations higher that 2.5%, presented total inhibition ability. Treatment with infusion using the highest concentration (10%) also showed positive response for B. cinerea growth inhibiting. The C. officinalis solutions presented induction capacity of the phytoalexins glyceolin in soybean cotyledons. It was observed that the solutions applied during the strawberry postharvest didn’t influence in the physico-chemical characteristics (mass loss, rots incidence, titratable acidity, flesh firmness and total soluble solids). In the biochemical analyzes for totals sugars and anthocyanins wasn’t observed statistical difference among the treatments. The alcoholic extract all over the concentrations and the infusion with concentrations higher than 5% stimulated the flavonoids productions. The PAL enzyme activity was stimulated by the application of extracts.